Crystal facet and phase engineering for advanced water splitting. Issue 33 (8th August 2022) - Lee, Mi Gyoung; Yang, Jin Wook; Kwon, Hee Ryeong; Jang, Ho Won
Abstract : This review covers the principles and recent advances in facet and phase engineering of catalysts for photocatalytic, photoelectrochemical, and electrochemical water splitting. It suggests the basis of catalyst design for advanced water splitting. Abstract : Water splitting is a promising approach to producing renewable hydrogen energy with zero carbon dioxide emission, and it has been intensively studied to improve conversion efficiencies over the past decades. As a result, crystal facet and phase engineering have been attracted as unique strategies for designing (photo)electrocatalysts. However, there are few specialized review articles on facet and phase engineering for various water splitting systems so far. In this review, we start by concisely introducing the principle of three water splitting systems. The subsequent section explains notable tactics of crystal facet and phase engineering to modify the intrinsic properties of catalysts and construct the junction. Then, we discuss recent advances in facet and phase-engineered catalysts for water splitting. Finally, the last section outlines the challenges and invigorating perspectives for future research on crystal facets and phase-engineered catalysts for practical water splitting systems. We believe this review enables us to strengthen the basis of crystal facet and phase engineering to promote the development of water splitting cells.